Teaching Skills Level of Female Student Teachers at The University of Petra and its relation to the GPA - Ajaj, Munier (Advances in Social Sciences Research Journal, 2018)
This study aimed at knowing the teaching skills level of female student teachers who are specializing in Class Teacher at University of Petra, and its relation to the GPA. The study sample consisted of 58 female student teachers who are registered in training course of the second semester for the academic year 2016/2017. The two researchers prepared an observation sheet that covers five aspects: planning, teaching procedure (Implementation), evaluation, lesson closure, and class management. The study results indicated an average practice of teaching skills as shown by the female student teachers with an Arithmetic Average of (2.468). Whereas, the performance of the observed sample was high in the areas of teaching procedure and evaluation, average performance in the areas of planning and classroom management, and weak performance in the area of lesson closure. Also, the study results showed no statistical indicative differences attributed to the (GPA).